Adaptation Finance Landscape in India: Trends, Challenges and Way Forward - Acharya, Pracheta (International Journal of Environmental, Sustainability, and Social Science, 2026)
In the face of growing climatic threats, adaptation, and mitigation strategies have secured a significant place in the global discussions. In a developing country like India, adaptation is crucial to reduce the risk of grassroots communities, carrying the double burden of poverty and climatic vulnerabilities. India, the largest economy from South Asia is potential of setting an example for the Global South in terms of climate change actions. However, executing the actions requires sufficient finance flow as a pre-requisite condition. The commentary briefly offers an overview of the current adaptation finance scenario in India and identifies the major obstacles in mobilising funds to the adaptation sector. India’s adaptation finance is overdependent on the union budget due to a lack of availability and accessibility of the international multi development funds. The meagre involvement of the private sector in the adaptation financing in India puts further pressure on the limited investment capabilities of the government. The definitional ambiguity and the integrated nature of development and adaptation in India make it difficult to track the finance. The issue is further compounded by the weak governance. The resultant climate change adaptation gap provides a glimpse of this whole scenario.